2012
DOI: 10.1111/j.1600-0579.2012.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective and ineffective supervision in postgraduate dental education: a qualitative study

Abstract: Participants' responses provided rich, in-depth insights into their reflections and understandings of effective and ineffective approaches to supervision as it influenced their learning in the clinical and research settings. These findings provide a starting point for the development of curriculum and supervisory practices, enhancement of supervisory and mentoring approaches, and the design of continuing education programmes for supervisors at an institutional level. Additionally, these findings might also sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Present study results concur with these findings and also indicated a need for development of teacher curriculum and supervisory practices that would include enhancement of mentoring skills. In‐house teacher learning at institutions is recommended for clinical instructors …”
Section: Discussionmentioning
confidence: 99%
“…Present study results concur with these findings and also indicated a need for development of teacher curriculum and supervisory practices that would include enhancement of mentoring skills. In‐house teacher learning at institutions is recommended for clinical instructors …”
Section: Discussionmentioning
confidence: 99%
“…The professional expertise of the FB provider was recognised by the dental students . Students reflected that they profited from the clinical experience of the FB provider . Both FB providers were motivated and convinced of the usefulness of FB .…”
Section: Discussionmentioning
confidence: 99%
“…Special attention was given to provide valid and relevant content in the FB because invalid and irrelevant FB not only impairs learning but also interferes with the processing of relevant FB . FB was given individually , based on the directly observed personal performance of the dental student . Assisted by the assessment tool, observations, documentation and FB dialogue were well structured , combining grading with non‐graded evaluation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The program content focused on supervisory skills and on improving clinical teaching in general, as suggested by the leadership of the teaching clinics and the literature (19)(20)(21)(22)(23)(24)(25). Specific content needs expressed by the participants at the start of the program were integrated into the program.…”
Section: The Faculty Development Programmentioning
confidence: 99%